1999
DOI: 10.1073/pnas.96.10.5764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of juvenile hormone on the central nervous processing of sex pheromone in an insect

Abstract: Behavioral sex pheromone responsiveness in the male moth Agrotis ipsilon was previously shown to be controlled by juvenile hormone (JH). However, this morphogenetic hormone did not change the sensitivity of antennae to sex pheromones. To analyze the possible involvement of JH in the central integration of the female-produced sex pheromone, we investigated the pheromone response of olfactory antennal lobe (AL) interneurons in male A. ipsilon as a function of age and JH status by using intracellular recordings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 28 publications
3
83
1
1
Order By: Relevance
“…The general response pattern was similar to that observed previously; neurons responded generally with an excitatory response, characterized by a fast increase in AP frequency, followed by an inhibitory period devoid of APs (Anton and Gadenne, 1999;Gadenne and Anton, 2000;Jarriault et al, 2009b). In virgin males (N=60, 33, and 38 neurons for NaCl-, OA-and 5-HT-injected males, respectively), there was no statistical difference in AL neuron response threshold between NaCl-injected males, and OA-and 5-HT-injected males (G=1.2, P>0.05); all males showed a high proportion of very sensitive neurons (with a low response threshold) (Fig.…”
Section: Effects Of Oa and 5-ht On Al Neuron Sensitivity To Sex Pherosupporting
confidence: 84%
See 2 more Smart Citations
“…The general response pattern was similar to that observed previously; neurons responded generally with an excitatory response, characterized by a fast increase in AP frequency, followed by an inhibitory period devoid of APs (Anton and Gadenne, 1999;Gadenne and Anton, 2000;Jarriault et al, 2009b). In virgin males (N=60, 33, and 38 neurons for NaCl-, OA-and 5-HT-injected males, respectively), there was no statistical difference in AL neuron response threshold between NaCl-injected males, and OA-and 5-HT-injected males (G=1.2, P>0.05); all males showed a high proportion of very sensitive neurons (with a low response threshold) (Fig.…”
Section: Effects Of Oa and 5-ht On Al Neuron Sensitivity To Sex Pherosupporting
confidence: 84%
“…Our results showed that both OA and 5-HT had no effect on the response threshold of AL neurons of virgin males to pheromone, presumably because the AL sensitivity of mature virgin 5-day-old males is already at its maximum, as compared with the low AL sensitivity of immature 1-day-old males or newly mated males, where sensitivity can be increased by amine injection (Anton and Gadenne, 1999;Gadenne et al, 2001;Jarriault et al, 2009a). However, OA induced changes in all four AL neuron response characteristics analyzed here whereas 5-HT only changed the response latency to sex pheromone.…”
Section: Oa and 5-ht Modulate Sex Pheromone Response Characteristics mentioning
confidence: 53%
See 1 more Smart Citation
“…This adult volume gain can be induced up to a critical age by specific odors and, unlike pupal growth, seems to involve a cAMPdependent signalling pathway (Devaud et al 2001). In Agrotis ipsilon pheromone-specific odor processing seems to be dependent upon juvenile hormone and age (Anton and Gadenne 1999;Gadenne and Anton 2000;Greiner et al 2002). Two main possibilities may explain the induction of adult neuropilar growth: first, it might represent the final maturation processes, which are possibly hormonally controlled, or second, it might be a manifestation of early adult neural plasticity depending on sensory input (as discussed in Julian and Gronenberg 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly known for its role in metamorphosis, reproduction and more recently longevity (Flatt et al, 2005). Interestingly, JH has been shown to modulate olfactory interneuron sensitivity to pheromones in locust (Anton and Gadenne, 1999). In honeybees, high JH levels are also known to increase foraging activity (Robinson, 1985), whereas it lowers the sensitivity threshold to sugar (Pankiw and Page, Jr, 2003).…”
Section: Why Do To 1 Flies Die Faster Than Wt During Starvation?mentioning
confidence: 99%